Uncovering Gender-Role Differences in Reflective Thinking: A Qualitative Study of Prospective Teachers Solve Open-Ended Mathematics Problems - Zainal Abidin; I Ketut Budayasa; Siti Khabibah (International Journal of Research and Community Empowerment, 2026)
Reflective thinking is a critical cognitive process that supports students in analysing, monitoring, and evaluating their reasoning when solving mathematical problems. This study aims to reveal differences in prospective teachers’ reflective thinking when solving open-ended mathematics problems. This qualitative case study involved two prospective teachers representing masculine male and feminine female gender-role orientations. Subjects were selected based on a gender questionnaire and mathematical ability. Instruments included a gender questionnaire, problem-solving tasks, and semi-structured interviews. Data were analysed through classification, reduction, presentation, interpretation, and conclusion drawing, with credibility ensured through time triangulation. The results indicate that the masculine male participant demonstrated a more systematic and complete reflective thinking profile, articulated logical justifications, and explored alternative strategies. In contrast, the feminine female participant presented incomplete and unsystematic steps, with limited logical reasoning and strategic variation. These findings show that gender-role orientation qualitatively influences reflective thinking in solving open-ended problems. This study contributes to Sustainable Development Goal 4 (Quality Education) by providing insights for designing gender-responsive and adaptive mathematics instruction to strengthen prospective teachers’ reflective thinking and promote equitable learning quality.